2014
DOI: 10.1515/pac-2014-0110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of cadmium bioaccumulation in three Mediterranean marine bivalve species: correlation with selected biomarkers

Abstract: An ecotoxicological study is presented, in which three marine bivalve species (Mytilus galloprovincialis, Callista chione, and Venus verrucosa) living in different habitats were studied for Cd bioaccumulation, under laboratory conditions. The bivalves, originating from a relatively polluted marine area of Greece (Saronicos Gulf), were exposed to 0.5 mg Cd L–1 seawater (4.4 mol Cd L–1 seawater) for 5, 10, 15, and 20 days. Control animals were kept in metal-free seawater as well. Three or four different parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…galloprovincialis (Chalkiadaki et al, 2014), our results confirmed that AChE in mussels is not sensitive to Cd exposure in vivo, probably due to the well known efficient detoxification mechanism of Cd by MTs (Pytharopoulou et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…galloprovincialis (Chalkiadaki et al, 2014), our results confirmed that AChE in mussels is not sensitive to Cd exposure in vivo, probably due to the well known efficient detoxification mechanism of Cd by MTs (Pytharopoulou et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…This period corresponds to the "sexual rest stage" and ensures a lack of inherent differences in the physiological status of males and females due to gametogenesis (Da Ros et al, 1985;Jarque et al, 2014). Collected organisms were rapidly moved to the laboratory and acclimated for 5 d at controlled physicochemical conditions in line with previous studies (Chalkiadaki et al, 2014;Nogueira et al, 2017). During this period mussels were maintained at 16 °C in multi-mesh filtered seawater (FSW) collected from the same area as the mussels to minimize the presence of organic matter and facilitate the organisms' acclimation.…”
Section: Mussel Acclimation and Experimental Treatmentsmentioning
confidence: 99%
“…Clams exposed to 40 µg/L Cd had depressed O:N ratio and SFG throughout the exposure and depuration, and SFG was negative for days 21 to 35 of exposure, indicating that the clams were unable to obtain enough energy to fuel their metabolic requirements. Chalkiadaki et al (2014) 9 HSP genes were also examined, Cu affected the most genes, and hsp20 and especially hsp70 were found to be the most sensitive genes to all five metals. Heat shock protein 20 expression was also found to be sensitive to Cu as well as Ni in the diatom Ditylum brightwelii, but expression was not sensitive to bisphenol A, Arochlor 1016 or endosulfan (Lee, Guo and Ki 2014).…”
Section: Personal Care Productsmentioning
confidence: 99%
“…depressed O:N ratios (a measure of energy source) from day 7 of exposure to 15 days after removal of Cd, and depressed SFG from day 21 of exposure to 7 days after removal). Clams exposed to 40 µg/L Cd had depressed O:N ratio and SFG throughout the exposure and depuration, and SFG was negative for days 21 to 35 of exposure, indicating that the clams were unable to obtain enough energy to fuel their metabolic requirements Chalkiadaki et al (2014). exposed the bivalves Mytilus galloprovincialis, Callista chione and Venus verrucosa to 0.5 mg/L Cd for 20 days followed by 10 to 30 days depuration.…”
mentioning
confidence: 99%